2014
DOI: 10.1016/j.buildenv.2014.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rainfall on the noise shielding by a green roof

Abstract: The potential of a green roof to reduce diffracting sound waves towards a shielded side of a building has been assessed before by both in-situ and laboratory experiments, and by numerical simulations. However, like any porous material, the acoustic performance of the green roof's substrate could suffer from the presence of water. A 46-day lasting controlled sound propagation experiment was set up near the edge of a 6-m tall building equipped with an extensive green roof, having a substrate thickness of 7 cm. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
0
11
0
5
Order By: Relevance
“…Long-term in-situ experimentations were also conducted on green roofs incorporating relatively heavy substrates to evaluate the variation of acoustic signal attenuation with substrate water content. Van Renterghem and Bottledooren reported variations reaching 10 dB between dry substrate and moistened substrate close to saturation in the 250-1250 Hz frequency range [20]. Liu and Hornikx performed similar experiments for two roofs incorporating different substrates [21].…”
Section: Introductionmentioning
confidence: 90%
“…Long-term in-situ experimentations were also conducted on green roofs incorporating relatively heavy substrates to evaluate the variation of acoustic signal attenuation with substrate water content. Van Renterghem and Bottledooren reported variations reaching 10 dB between dry substrate and moistened substrate close to saturation in the 250-1250 Hz frequency range [20]. Liu and Hornikx performed similar experiments for two roofs incorporating different substrates [21].…”
Section: Introductionmentioning
confidence: 90%
“…A long-term in situ diffraction experiment 34 near the edge of a building equipped with an extensive green roof, subject to natural precipitation, showed that sound propagation was mainly sensitive to the volumetric water content (VWC) of the substrate in a particular frequency range, namely between 250 and 1250 Hz. 34 The difference in the noise attenuation between 10% VWC (relatively dry state) and a fully saturated condition ranged up to 10 dB. 34 However, the impact of the substrate's water content on the overall A-weighted road traffic noise abatement was predicted to be rather limited (less than 1.5 dBA).…”
Section: Measurementsmentioning
confidence: 99%
“…34 The difference in the noise attenuation between 10% VWC (relatively dry state) and a fully saturated condition ranged up to 10 dB. 34 However, the impact of the substrate's water content on the overall A-weighted road traffic noise abatement was predicted to be rather limited (less than 1.5 dBA). 34…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the acoustic perspective, the insulation capability of the vegetated roof is generally recognized to be a function of the growing substrate thickness and density [23], while the acoustic absorption coefficient is mostly affected by the organic content, and by the ground compaction level [22]. Additionally, both properties seem to be somehow influenced by the water content in the substrate itself [30].…”
mentioning
confidence: 99%